2014
DOI: 10.1177/1529100614541236
|View full text |Cite
|
Sign up to set email alerts
|

Women in Academic Science

Abstract: Much has been written in the past two decades about women in academic science careers, but this literature is contradictory. Many analyses have revealed a level playing field, with men and women faring equally, whereas other analyses have suggested numerous areas in which the playing field is not level. The only widely-agreed-upon conclusion is that women are underrepresented in college majors, graduate school programs, and the professoriate in those fields that are the most mathematically intensive, such as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
329
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 792 publications
(439 citation statements)
references
References 209 publications
20
329
1
6
Order By: Relevance
“…In contrast, no such effects were found for grade 4-6 students who observed a male or female model solving fraction problems . Although mathematical tasks are typically more associated with males than females (Forgasz et al 2004;Stewart-Williams 2002), young children do not yet seem to hold this association, which becomes stronger during adolescence (Steffens et al 2010; see also Ceci et al 2014). In other words, the 10 year olds in the study by Schunk et al (1987) More recent studies also suggest mixed findings, however.…”
Section: Model-observer Similaritymentioning
confidence: 54%
“…In contrast, no such effects were found for grade 4-6 students who observed a male or female model solving fraction problems . Although mathematical tasks are typically more associated with males than females (Forgasz et al 2004;Stewart-Williams 2002), young children do not yet seem to hold this association, which becomes stronger during adolescence (Steffens et al 2010; see also Ceci et al 2014). In other words, the 10 year olds in the study by Schunk et al (1987) More recent studies also suggest mixed findings, however.…”
Section: Model-observer Similaritymentioning
confidence: 54%
“…Throughout the undergraduate experience, women in STEM are more likely to face subtle bias from their peers and faculty that may have lasting negative impacts on academic performance and measures of active inclass participation (15)(16)(17). The outcome is female attrition along the STEM pathway, such that at the faculty level, only one third across geoscience and life science disciplines are women (18). This further disadvantages female undergraduates, who disproportionately benefit by having women in positions of authority within their discipline; female faculty are more likely to serve as mentors for women (19), and their presence increases female students' confidence in their ability to do science (7), science identities (20), and their performance (21)(22)(23)(24) and persistence (25) in STEM.…”
Section: Introductionmentioning
confidence: 99%
“…Mobility is a particular issue when women have partners and families. It has been shown that women scientists frequently marry other scientists (Mason and Goulden 2004;Ceci et al 2014), more so than men. This presents issues of dual careers.…”
Section: Women and Academic Careersmentioning
confidence: 99%
“…As well as possibly less hours worked, this could also be due to having less time to network. This may include socializing after work or at weekends (Ackers 2007), when people, especially women with small children, may not be available (Ceci et al 2014). Women might suffer lack of progression because they take time out for maternity or reduce their hours to care for children even temporarily.…”
Section: Women and Academic Careersmentioning
confidence: 99%
See 1 more Smart Citation